Affectionately yours, Screwtape : [videorecording (DVD)] : the devil and C.S. Lewis / C.S. Lewis ; written by Tom and Amy Dallis. - Lewis, C. S. (Clive Staples), 1898-1963 (Vision Media, 2007)
A modern look at C.S. Lewis's timeless classic, The Screwtape letters, which is a thin volume of imaginative letters between two devils.